PENGARUH TEKNIK BRAINSTORMING DALAM BIMBINGAN KELOMPOK TERHADAP MOTIVASI BELAJAR SISWA SMP NEGERI 4 PALOPO - Azzahra, Dita Aprillia; Fahmi, Ainul; Nurhayati, Andi; Bin Anwar, Arman (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to determine the extent of the influence of brainstorming techniques in group guidance services on student learning motivation at SMP Negeri 4 Palopo. The background comes from the low motivation of students to learn which can be seen from the lack of participation in the learning process, lack of interest in the subject matter, and the tendency to be passive in the classroom. Through participatory approaches such as brainstorming, students are given the space to express their ideas, opinions and experiences freely without fear of being judged, which is expected to increase their enthusiasm and engagement in learning. This study used a quantitative method with a one group pretest-posttest quasi experimental design. A sample of 20 students was purposively selected based on the level of motivation which was classified as low to moderate. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability, then analyzed with the Paired Sample T-Test test through the SPSS program. The results showed a significant increase in student learning motivation after being given the treatment, with an average pretest score of 41 which increased to 51.35 in the posttest, and a significance value of 0.000. These results prove that the brainstorming technique is effective in increasing students' learning motivation and can be an alternative group guidance service strategy.